Level of Implementation of Safekeeping Practices in the Bureau of Jail Management and Penology - Nicholas, Elrhine D.; Pallega, Rowell B.; Comecilla, Meynard O. (International Journal of Multidisciplinary: Applied Business and Education Research, 2022)
This study aimed to determine the level of implementation of safekeeping practices in the Bureau of Jail Management and Penology in Ipil District Jail and Ipil Women’s Dormitory Jail of Zamboanga Sibugay during calendar year 2018-2019. This study made use of non-experimental quantitative research design utilizing descriptive, frequency count, percentage and mean. It also utilized modified questionnaire in gathering the result. There were 127 inmates and 50 Bureau of Jail Management and Penology personnel utilized as respondents of the study. The main statistical tools used were frequency count, percentage, mean computation, t-test, analysis of variance and Pearson r Product Moment Coefficient of Correlation. The study revealed that there were more male inmates as compared to the females. Majority of the index crimes committed by the inmates were murder while on the non-index crimes, majority were charged against possession of illegal drugs. The security practices were always implemented by the two Jail under study which included the following: Commitment Order and Segregation of Prisoners or Detainees, Reception Procedures, and Disciplinary Boards and Punishable Acts of Inmates, Treatment of Inmates with Special Needs, Custody, Security and Control Emergency Plans, Movement and Transfer of Prisoners and Detainees, Rights, Privileges and Miscellaneous Provisions, and Inmates Welfare and Development Functions. There was no significant difference between the Bureau of Jail Management and Penology and inmate’s ratings on the implementation of commitment order and segregation of inmates or detainees. However, there was a significant difference between the Bureau of Jail Management and Penology and inmates’ rating on the rest of the safekeeping practices. Indeed, there was a significant relationship between the safekeeping practices and the level of Implementation of these practices. The researcher recommends that the Bureau of Jail Management and Penology implementation of safekeeping practices be continued and sustained.